The Assessment for Learning Practices of Project-Based Learning in the English Research Class - Kamea, Fintha (Foremost Journal, 2025)
Research on Assessment practices in ELT of Project Based Learning approach is increasing because it is considered effective in creating a learning environment that is oriented towards continuous improvement. To get satisfactory results, the researcher decided to identify how one of the ELT lecturers at Esa Unggul University conducts assessment by implementing Assessment for Learning in Project Based Learning by focusing this research on the research method class because the class applies the Project Based Learning approach. The research was conducted by analyzing teaching documents in the form of 1 syllabus and project guidebook of 49 pages, then observing 3 videos of lecturers during class teaching based on 14 indicators and finally analyzing interview transcripts with lecturers consisting of 14 questions. The results of the study identified that lecturers overall implemented and practiced the types of Feedback and Questioning, but lecturers still rarely and slightly involved the use of Self-Assessment and Peer Assessment as indicators of student assessment.